İklim Değişikliği Çerçevesinde Ankara İli Ana Su Havzaları Gelecek Projeksiyonu: Sakarya ve Batı Karadeniz Havzaları - M. Murat Kale (Coğrafi Bilimler Dergisi, 2020)
In this study; the impact of global climate change on the water resources of Ankara, located in the Sakarya and Western Black Sea basins, was investigated. In the study, IPCC AR4 and AR5 scenario outputs and long term precipitation and temperature datasets were used together. The main source of the water in the sub-basins where the regulators and dams are located is the precipitation in the winter and spring seasons. According to the results of the study, at the end of the projection period, precipitation anomalies in the sub-basin where the regulator is located reach up to10% in the winter season. In the same basin, precipitation anomalies in spring season ranging from - 20% to 10% are expected. At the end of the projection period, in the winter season it is expected that reach up to 10% in the sub-basins where the dams are located. In the spring season, negative precipitation anomalies are expected, up to 10% according to SRES A2 outputs and varying according to other scenario outputs. At the end of the projection period, temperature anomalies are expected between 2° C and 6°C in winter and spring seasons.